2012
DOI: 10.1007/s11250-012-0316-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substituting soya bean meal (SBM) with blood meal (BM) on biochemical profile of pregnant pigs

Abstract: Twenty-four Large White × Landrace crossbreed primigravid pigs, aged 7.50 to 8.00 months weighing between 86.15 and 88.24 kg were used to study the effects of feeding graded levels of soya bean meal (SBM) replaced blood meal (BM) diets on serum biochemical profile in gestating pigs. The pigs were randomly allotted to four finisher diets formulated such that BM replaced SBM at 0.0, 50.0, 75.0 and 100.0 %, respectively. The diets were T1 (100.0 % SBM, 0.0 % BM), T2 (50.0 % SBM, 50.0 % BM), T3 (25.0 % SBM, 75.0 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
3
5
0
Order By: Relevance
“…This result support the previous report of Serment et al (2011). Abonyi et al (2013), Chen et al (2015) and Dong et al (2017) who revealed that the high concentrate diet probably improved energy balance, protein synthesis and humoral immunity of the animal. Blood urea nitrogen (BUN) concentration was used as indicator of nitrogen utilization efficiency by ruminants (Lewis, 1957).…”
Section: Blood Metabolitessupporting
confidence: 92%
“…This result support the previous report of Serment et al (2011). Abonyi et al (2013), Chen et al (2015) and Dong et al (2017) who revealed that the high concentrate diet probably improved energy balance, protein synthesis and humoral immunity of the animal. Blood urea nitrogen (BUN) concentration was used as indicator of nitrogen utilization efficiency by ruminants (Lewis, 1957).…”
Section: Blood Metabolitessupporting
confidence: 92%
“…The lower plasma urea N of goats fed PT leaves suggests reduced ruminal NH 3 -N levels, in accordance with previous findings where jackfruit and Barhar leaves replaced concentrates (Das & Ghosh 2007;Das et al 2011). Lack of treatment effect on plasma protein indices, which were within the normal ranges (Fraser & Mays 1986), indicates adequate humoral immunity and protein synthesis of the animals (Abonyi et al 2013). The lower serum urea N of PT diets, therefore, indicates the superiority of its protein relative to the concentrate, since serum urea N is a product of protein and amino acid catabolism in the body and negatively correlates with nitrogen deposition and protein or amino acid utilization (Olafadehan 2011a;Chen et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Since glucose and cholesterol levels were within the normal ranges, possibilities of anorexia, diabetes, liver dysfunction and malabsorption of fat, which are the symptoms of abnormal glucose and cholesterol levels in the blood ( Zub ci c 2001) are ruled out. Lack of treatment effect on plasma protein indices, which were within the normal ranges (Fraser & Mays 1986), indicates adequate humoral immunity and protein synthesis of the animals (Abonyi et al 2013). Similar serum mineral values of all the animals suggest that concentrate replacement with PT leaves did not interfere with the availability and absorption of major serum minerals, because the values were within the normal ranges for healthy goats (Sirois 1995).…”
Section: Discussionmentioning
confidence: 97%
“…The increase in plasma glucose concentration reflects higher hepatic glucogenesis (Bobe et al, 2004), associated with the higher propionate proportion observed in our study. This result support the previous report of Serment et al (2011) , Abonyi et al (2013), Chen et al (2015) and dong et al (2015) who revealed that the high concentrate diet probably improved energy balance, protein synthesis and humoral immunity of the animal. Blood urea nitrogen (BUN) concentration was used as indicator of nitrogen utilization efficiency by ruminants (Lewis, 1957).…”
Section: Blood Metabolitessupporting
confidence: 92%